Association between prognostic nutritional index and all-cause mortality and cardiovascular disease mortality in American adults with non-alcoholic fatty liver disease - Lei, Yuqing; Tao, Shaohong; Yang, Yubo; Xie, Fang; Xie, Weining (Frontiers in Nutrition, 2025)
BackgroundThe current research was to investigate the relationship between prognostic nutritional index (PNI) and mortality, with a focus on all-cause and cardiovascular disease (CVD) mortality, for those with non-alcoholic fatty liver disease (NAFLD).MethodsData from 20,142 patients who participated in the National Health and Nutrition Examination Survey (NHANES), which was carried out between 2005 and 2014, were included in this research. To examine the relationship between PNI and both all-cause and cardiovascular mortality, we employed weighted Cox regression models with multiple variables. Kaplan–Meier survival curves were utilized to visualize the survival distribution across different levels of PNI. The non-linear association between PNI and mortality was addressed through penalized spline smoothing. Subgroup analyses were conducted to examine the potential influence of relevant clinical variables on the relationship between PNI and mortality. The precision of PNI in forecasting the outcome of survival was assessed as well using time-dependent receiver operating characteristic curve (ROC) analysis.ResultsKaplan–Meier analysis linked higher PNI to significantly reduced all-cause and CVD mortality. Multivariable Cox models demonstrated that increasing PNI consistently lowered mortality risks. With a threshold value of 50.5, the link between PNI and mortality showed a non-linear pattern after adjusting for confounding factors. Subgroup analyses confirmed robust associations, particularly in race, education, BMI, and fibrosis. Time-dependent ROC analysis highlighted the strong predictive performance of PNI across various time points.ConclusionPNI played a significant role as an effective predictor of prognosis in individuals diagnosed with NAFLD.